Evolving Antithrombotic Treatment Patterns for Patients With Nonvalvular Atrial Fibrillation and Acute Coronary Syndrome or Underwent Percutaneous Coronary Intervention in China: A Cross-Sectional Study - Suo, Ni; Yang, Yan-min; Wang, Juan; Zhang, Han; Shao, Xing-hui; Wu, Shuang; Zhu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Objective Antithrombotic therapy in patients with nonvalvular atrial fibrillation (NVAF) concomitant with the acute coronary syndrome (ACS) or underwent percutaneous coronary intervention (PCI) is challenging and has evolved in recent years. However, real-world data on this issue about antithrombotic regimens at discharge and its evolving trend were relatively scarce, especially in China. Methods A total of 2,182 patients with NVAF and ACS/PCI were enrolled from 2017 to 2019. A total of 1,979 patients were finally analyzed and divided in three sequential cohorts: cohort 1 (2017), n = 674; cohort 2 (2018), n = 793; and cohort 3 (2019), n = 512. Baseline characteristics and antithrombotic therapy at discharge were analyzed by cohort. Results In our cross-sectional study, the majority of patients (59.6%) received dual antiplatelet therapy (DAPT). Over the 3 years, DAPT prescription reduced from nearly 70% to <50% (P trend < 0.001), while triple therapy (TT)/double therapy (DT) increased from 27.2 to 50.0% (P trend < 0.001). This trend was also seen in different subgroups stratified by CHA2DS2-VASc score, HAS-BLED score, coronary artery disease type, or management type, and was validated after multivariate adjustment. Persistent atrial fibrillation and history of congestive heart failure, hypertension, diabetes mellitus, and stroke/transient ischemic attack/systemic embolism were the independent predictors of TT/DT use, while ACS, PCI, or advanced chronic kidney disease was related with more DAPT prescription. Conclusion There is a shift of antithrombotic regime at discharge for patients with NVAF with recent ACS/PCI with reducing DAPT prescription and increasing TT/DT prescription. While the appropriate antithrombotic regimen for patients with NVAF having ACS/PCI is still underused in China.